Vitamin D supplementation and moderate intensity continuous training: Impact on leptin and anthropometric measures in obese individual - Suputra, Putu Adi; Arsani, Ni Luh Kadek Alit; Wijaya, I Made Kusuma; Lestari, Ni Made Sri Dewi; Parwata, I Made Yoga (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Vitamin D may potentially have a significant influence in managing obesity-related risk factors. The current evidence suggests that observational studies have found a negative correlation between leptin levels and serum vitamin D, but heterogeneous intervention studies have not shown a significant effect. Objectives: This study aims to examine the effect of the combination of moderate-intensity continuous training (MICT) and vitamin D3 on leptin and anthropometry. Methods: A true experimental, randomized pre and post-test control group design were performed on 36 subject (18 male and female each) for 12 weeks. A treatment group received MICT and vitamin D3, control group only received MICT and placebo. Both groups received moderate-intensity exercise (64-75% HR Max) with a frequency of 3x/week and a time of 60 minutes, carried out. In the treatment group, 5000 IU vitamin D3 was administered daily for 12 weeks, while the control group only received a placebo. In this study, hypothesis testing was conducted to compare the means of two independent groups using an independent t-test or Mann-Whitney test. For comparisons between two related groups, a paired t-test or the Wilcoxon Signed Rank Test was used.Results: After conducting a test to compare two sample means from unrelated groups, statistically significant differences were observed between the treatment and control groups in this study. For the variables of BMI (p=0.025), waist circumference (p=0.042), body weight (p=0.008), leptin (p=0.015) and vitamin D3 (p<0.001). Conclusion: Combination of vitamin D3 supplementation and MICT significantly lowered leptin and anthropometry in obese individuals.